Pengaruh Perceived Price dan Delivery Quality terhadap Repeat Purchase Intention: Peran Perceived Value dan Consumer Satisfaction - Anisah Saniyyah; Unggul Kustiawan (ARZUSIN, 2025)
E-commerce has become a dominant platform in modern consumer shopping behavior; however, the low level of repeat purchase intention remains a significant challenge for digital business operators. This study aims to analyze the influence of perceived price and delivery quality on repeat purchase intention, considering the mediating roles of perceived value and consumer satisfaction among e-commerce users in Bekasi City. A quantitative approach was employed using an online survey method through a questionnaire distributed to 110 respondents selected via purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results indicate that both perceived value and consumer satisfaction have a significant positive effect on repeat purchase intention. Perceived price significantly influences perceived value and consumer satisfaction, while delivery quality has a positive effect on perceived value but does not significantly affect consumer satisfaction. These findings suggest that perceived value and consumer satisfaction are key determinants in shaping repeat purchase intention on e-commerce platforms. Therefore, implementing competitive pricing strategies, improving service quality, and managing customer experience holistically are essential to strengthening consumer loyalty in the digital era.